(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This study aims to strengthen parental literacy in preventing sexual violence and child marriage through a community-based intervention at Krapyak Kidul Public Health Center, Pekalongan. The program involved 20 parents and employed interactive lectures, Focus Group Discussions (FGD), communication simulations, and pre-test and post-test evaluations. The results showed a significant improvement in participants’ knowledge, with post-test scores increasing from an average range of 7–9 to 9–10. Overall, 85% of participants demonstrated improved literacy. These findings indicate that literacy-based education combined with practical simulation is effective in enhancing parents’ roles in protecting children from sexual violence and early marriage.